Poly[MWCNT/Imidoselenium] nanocomposite: Preparation, Characterization and DC Electrical Conductivity - Obeid, Abeer; Al-Yusufy, Fatima; Al-Aghbari, Sama; Al-Shuja'a, Omar; Gabr, Yassin; Al-Washal, Zinab (Research India Publications, 2020)
The chemical functionalization of amino multiwalled carbon nanotubes (MWCNT-NH2) by selenium dioxide (SeO2) was used to produce Poly [MWCNT/Imidoselenium] nanocomposite. The obtained poly-composite was characterized by FT-IR, UV-Vis, XRD, TEM, SEM, TGA, DSC and DC electrical conductivity. The characteristic peaks in FT-IR and UV-Visible spectra were found shifted to higher wave numbers, and the n-? * bands were shifted to lower wavelengths (red shift), respectively, which confirmed the formation of imidoselenium bond in the Poly[MWCNT-N=Se] nanocomposite. Morphological characterization was done by using scanning SEM, TEM indicated a good dispersion phase in the poly-nanocomposite matrix. The Poly[MWCNT-N=Se] nanocomposite showed good thermal stability. The DC electrical conductivity of poly-nanocomposite was found to be 5.34 10-4 S/cm in ambient temperature. This is attributed to the interaction among the nanotubes.